Nonsense-mediated mRNA decay in Drosophila:at the intersection of the yeast and mammalian pathways. - Gatfield, D.; Unterholzner, L.; Ciccarelli, F.D.; Bork, P.; Izaurralde, E. (The EMBO Journal, 2003)
The nonsense-mediated mRNA decay (NMD) pathway promotes the rapid degradation of mRNAs containing premature stop codons (PTCs). In Caenorhabditis elegans, seven genes (smg1-7) playing an essential role in NMD have been identified. Only SMG2-4 (known as UPF1-3) have orthologs in Saccharomyces cerevisiae. Here we show that the Drosophila orthologs of UPF1-3, SMG1, SMG5 and SMG6 are required for the degradation of PTC-containing mRNAs, but that there is no SMG7 ortholog in this organism. In contrast, orthologs of SMG5-7 are encoded by the human genome and all three are required for NMD. In human cells, exon boundaries have been shown to play a critical role in defining PTCs. This role is mediated by components of the exon junction complex (EJC). Contrary to expectation, however, we show that the components of the EJC are dispensable for NMD in Drosophila cells. Consistently, PTC definition occurs independently of exon boundaries in Drosophila. Our findings reveal that despite conservation of the NMD machinery, different mechanisms have evolved to discriminate premature from natural stop codons in metazoa.